Avaliação do patrimônio geomorfológico potencial dos municípios de Coromandel e Vazante, MG - Oliveira, Paula Cristina Almeida de (2015)
The districts of Coromandel and Vazante in Minas Gerais present a wide geodiversity, due to the geological and geomorphological complexity of Faixa Brasília and São Francisco craton. Moreover, the study area is on the Speleological Province of Bambuí, one of the carstic provinces of Brazil, and for that reason it is rich with carstic features like caverns and many types of speleothems. The study area landscape is also rich with hills, waterfalls, rapids, lakes, among others, which are denominated here as geomorphological heritage, all with great didactic and tourist potential. In this way, this paper aims to work with interpretative and informative methods in order to develop the potential geomorphological heritage in the districts of Coromandel and Vazante, with a view to promoting this heritage as well as contributing to a better comprehension of it. For that reason, this paper seeks to identify and map the existing potential geomorphological heritage in the study area; analyze the methodologies for inventorying, characterization and evaluation of the existing geomorfological heritage, adapting them to the particularities of the study area, potentializing the didactic and tourist values; and lastly, to suggest geoconservation strategies to each of the places selected. After an extensive bibliographic research about the trinomial Geodiversity, Geoconservation and Geoturism, geomorphological heritage and environmental interpretation, some geomorphosites evaluation methodologies (inventorying and quantifying) have been adapted in order to be applied in the study area. Fourteen potential places of geomorphologic interest have been evaluated and only three of them are able to receive the proposals of evaluation and conservation. They are the caverns Gruta da Lapa Nova and Gruta da Lapa Velha in Vazante and Poço Verde in Coromandel. Among the interpretative methods selected we highlight production of leaflets, pocket guides, postcards, signs and informative and interpretative panels and a blog on the internet.